Is physical activity associated with resting heart rate in boys and girls? A representative study controlled for confounders - Edner F. Zanuto; Raphael M. Ritti-Dias; William R. Tebar; Catarina C. Scarabottolo; Leandro D. Delfino; Juliano Casonatto; Luiz Carlos M. Vanderlei; Diego Giulliano Destro Christofaro (Jornal de Pediatria, 2020)
Objective: Investigate the relationship between different domains of physical activity and resting heart rate (RHR) in boys and girls. Method: The sample included 1011 adolescents, aged between 10 and 17 years. RHR was measured by a heart rate monitor and physical activity was assessed in total and in three different domains (school, occupational, and sports practice) by a questionnaire. Anthropometry was directly obtained for body mass index and central fat. Ethnicity, sedentary behavior, and smoking habits were self-reported and used to adjust the analysis, through hierarchical linear regression. Results: Total physical activity was associated with low RHR in boys (β = −0.52; 95% CI: −0.92, −0.12) and girls (β = −0.67; 95% CI: −1.07, −0.28). Although sporting physical activities were associated with low RHR in both boys (β = −0.58; 95% CI: −1.05, −0.11) and girls (β = −0.87; 95% CI: −1.34, −0.39), occupational physical activity was related to low RHR only in boys (β = −1.56; 95% CI: −2.99, −0.14). Conclusion: The practice of physical activity in the sport practice domain and total physical activity were related to low RHR in both sexes, while occupational physical activities were associated with RHR only in boys. Resumo: Objetivo: Investigar a relação entre diferentes domínios de atividade física e frequência cardíaca de repouso (FCRep) em meninos e meninas. Método: A amostra incluiu 1.011 adolescentes, com idade entre 10 e 17 anos. A FCRep foi medida por um monitor de frequência cardíaca e a atividade física foi avaliada no total e em três diferentes domínios (escolar, ocupacional e prática esportiva) através de um questionário. A antropometria foi obtida diretamente para o índice de massa corporal e gordura central. Etnia, comportamento sedentário e tabagismo foram autorrelatados e usados para ajustar a análise, através da regressão linear hierárquica. Resultados: A atividade física total foi associada à baixa FCRep nos meninos (β = -0,52; IC95% -0,92; -0,12) e meninas (β = -0,67; IC95% -1,07; -0,28). Embora as atividades físicas esportivas estivessem associadas à baixa FCRep em ambos meninos (β = -0,58; IC95% -1,05, -0,11) e meninas (β = -0,87; IC95% -1,34, -0,39), a atividade física ocupacional estava relacionada à baixa FCRep apenas em meninos (β = -1,56; IC95% -2,99; - 0,14). Conclusão: A prática de atividade física no domínio da prática esportiva e a atividade física total foram relacionadas à baixa FCRep em ambos os sexos, enquanto as atividades físicas ocupacionais foram associadas à FCRep apenas em meninos. Keywords: Physical activity, Resting heart rate, Sedentary behavior, School, Palavras-chave: Atividade física, Frequência cardíaca de repouso, Comportamento sedentário, Escola